2005
DOI: 10.1007/bf02969360
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of memory by dieckol and phlorofucofuroeckol in ethanol-treated mice: Possible involvement of the inhibition of acetylcholinesterase

Abstract: Phlorotannins, the polyphonic compounds found in brown Eisenia and Ecklonia algae, have several pharmacologically beneficial effects such as anti-inflammation. In addition, our recent data show that these compounds may improve the cognitive functions of aged humans suggesting the potential ability to enhance memory in several neurodegenerative disorders. To examine the experimental hypothesis that two effective components of Ecklonia cava, dieckol and phlorofucofuroeckol (PFF), have memory-enhancing abilities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 19 publications
4
65
0
Order By: Relevance
“…17) Phlorotannins are secondary metabolites polymerizing phloroglucinol (1,3,5-trihydroxybenzene) through an ether, phenyl, or 1,4-dibenzodioxin linkage. These polyphenolic compounds are responsible for a variety of bioactivities, including anti-diabetic complications, 17,18) and antitumorial, 19) hepatoprotective, 20) anti-plasmin inhibiting, 21) algicidal, 22) tyrosinase inhibiting, 23) antiinflammatory, 24,25) nitrite-scavenging, 26) anti-skin aging, 27,28) antioxidative, [29][30][31] anti-cholinesterase, 32,33) antiAlzheimer, 34) anti-hyperlipidemic, 35) anti-diabetic, [36][37][38][39] anti-allergic, 40) and angiotensin converting enzyme-I inhibitory activities. 41) As part of our continuous search for antidiabetic agents from natural sources, we investigated the MeOH extract and solvent-soluble fractions of the two selected brown algae, E. stolonifera and E. bicyclis, together with six isolated phlorotannins against -glucosidase and PTP1B.…”
Section: )mentioning
confidence: 99%
“…17) Phlorotannins are secondary metabolites polymerizing phloroglucinol (1,3,5-trihydroxybenzene) through an ether, phenyl, or 1,4-dibenzodioxin linkage. These polyphenolic compounds are responsible for a variety of bioactivities, including anti-diabetic complications, 17,18) and antitumorial, 19) hepatoprotective, 20) anti-plasmin inhibiting, 21) algicidal, 22) tyrosinase inhibiting, 23) antiinflammatory, 24,25) nitrite-scavenging, 26) anti-skin aging, 27,28) antioxidative, [29][30][31] anti-cholinesterase, 32,33) antiAlzheimer, 34) anti-hyperlipidemic, 35) anti-diabetic, [36][37][38][39] anti-allergic, 40) and angiotensin converting enzyme-I inhibitory activities. 41) As part of our continuous search for antidiabetic agents from natural sources, we investigated the MeOH extract and solvent-soluble fractions of the two selected brown algae, E. stolonifera and E. bicyclis, together with six isolated phlorotannins against -glucosidase and PTP1B.…”
Section: )mentioning
confidence: 99%
“…9) For example, an Ulva reticulata methanol extract 10) and phlorotannin compounds from Ecklonia stolonifera 11) have shown a neuroprotective effect by inhibiting acetyl cholinesterase and butyryl cholinesterase activities. Myung et al 12) have reported that dieckol and phlorofucofuroeckol produced memory-enhancing effects by inhibiting acetylcholinesterase activity in ethanol-treated mice. However, the depressive effects of marine plants on the central nervous system (CNS) have not been widely investigated.…”
mentioning
confidence: 99%
“…3). Protonated molecular ion at m/z 743 is suggested to be a polyphenolic compound composed by six phloroglucinol units (hexamer), which is supported by studies by Myung et al [14] and Kang et al [21]. Hereafter, these five peaks (m/z 128, m/z 157, m/z 186, m/z 373 and m/z 743) were compared with the known standards for the chemical + ) recorded at m/z 100-1000 range spectrum of the ethyl acetate fraction from green tea extract fingerprint confirmation of the ethyl acetate fraction of the green tea extract.…”
Section: Identification and Characterization Low Mw (Molecular Weightmentioning
confidence: 54%
“…Studies have shown that marine organisms including brown algae are important sources of new bioactive compounds. The main chemical constituents of brown algae are polysaccharides and polyphenols [14]. The polyphenolic compounds from brown algae are identified as phlorotannin on Sargassum kjellamanianum which is indicated as an antioxidant [2].…”
Section: Determination Of Total Phenolicmentioning
confidence: 99%